FDG PET/CT of Mediastinal Epithelioid Hemangioendothelioma. (September 2019) - Hod, Nir; Anconina, Reut; Levin, Daniel; Delgado, Bertha; Dudnik, Julia; Lantsberg, Sophie
Abstract : Abstract: Epithelioid hemangioendothelioma is a rare low- to intermediate-grade malignant vascular neoplasm with a variable clinical course and currently no standardized treatment. We present a case of a 65-year-old woman diagnosed as having mediastinal epithelioid hemangioendothelioma, a location which is very exceptional. FDG PET/CT was more sensitive than CT for staging, revealing intense FDG uptake in the primary tumor and in the metastatic disease. Despite high FDG uptake, the disease was stable with no further specific treatment. Only few reports utilizing FDG PET/CT are available; review of the literature on this subject is included.